Remittance or persistence of attention deficit–hyperactivity disorder (ADHD) and its impact on recidivism in risky driving behaviors. (3rd October 2018) - Valero, S.; Bosch, R.; Corominas, M.; Barrau, V.; Ramos-Quiroga, J. A.; Casas, M.
Abstract: Objective: Recent data regarding the persistence or remittance of attention deficit–hyperactivity disorder (ADHD) diagnosis into adulthood raise the question of its possible role in crucial public health issues, including road safety, especially when neurocognitive capacities are challenged. Methods: The study included 611 participants with serious traffic violations. The Spanish version of the Mini International Neuropsychiatric Interview (M.I.N.I.) was used to assess psychopathology. They were grouped into 3 diagnostic conditions: non-ADHD, persistent ADHD (ADHD-P), and remittent ADHD (ADHD-R). Several risky driving behaviors were analyzed. Results: Although participants with ADHD have more driving violations relative to non-ADHD, ADHD-R, and ADHD-P drivers have similar profiles. ADHD-R and ADHD-P drivers are more prone to perform risky and recidivistic behaviors relative to non-ADHD counterparts ( P  = .044 and P  = .047, respectively); ADHD-R and ADHD-P participants are statistically comparable in this proneness ( P  = .772). Conclusion: These results suggest that the underlying core deficits of ADHD—attention and other executive disabilities—persist despite the fact that some people no longer reach the threshold for clinical diagnosis.